The poor in Europe (Journal of Parents and Teachers, 2026)
In Europe, there are millions of people living in poverty, including the illiterate, the long-term unemployed, and the homeless. To try to mitigate this, various educational policies are being proposed to prevent these situations, including raising awareness and adapting programmes to individual learning speeds.
Keywords: Poverty; Exclusion; Integration; Education